The mephistophelian charm of the dialectic - Ponce Bogino, Héctor (2014)
Certain institutions in Peru, by imposing a strictly operational purpose, impinge on the teaching of literature and philosophy, of ethics and aesthetics, which are disciplines that refine our critical judgments. The humanities, for their part, struggle to highlight the value of its complexity by encouraging a reflection that ideally encompasses different viewpoints. In this article, the dialectic will be, first, a strategy in the search of agreements, and second, a radical reflection that can be ascorrosive as the satire. Finally, however, it will be showed that with the dialectic, one can run the risk of imprecision.